Environment and jurisdictional protection under a preventive perspective in cases of suicide - Castro, Bianca Andrade de; Cunha, Caroline Bianchi; Cansi, Francine (Seven Editora, 2023)
The proposal of the authors is to present the psychological, social and economic impacts caused by the environment in which we currently live, by the bias of the new legal and sociological treatment of ecological issues, the innovation of human rights, quality of life, the right to peace and the balance of ecosystems, among others. It also wants to demonstrate the historical concepts, the multidisciplinarity and the progressive increases in suicide rates, in the face of the consequences of these events within the perspective of the new sensibilities and cultural evolution of man-nature as a framework for the search for the environmental protection of ecology within the social, constitutional and technological sciences. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-044